Barack and Joe : the making of an extraordinary partnership - Levingston, Steven (Hachette Books, 2019)
The extraordinary partnership of Barack Obama and Joe Biden is unique in American history. The two men, their characters and styles sharply contrasting, formed a dynamic working relationship that evolved into a profound friendship. Based on original interviews, media reports, memoirs and other accounts, Barack and Joe is the first book to tell the full story of their historic relationship and its substantial impact on the Obama presidency and its legacy.